Demodex infections in general polish population, in patients suffering from blepharitis, and among people who work with microscopes - Garbacewicz, Aleksandra; Udziela, Monika; Grytner-Zięcina, Barbara; Szaflik, Jacek P.; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
In this study we examined 264 people to estimate the prevalence of Demodex infection. The subjects were divided into 4 groups. First two groups consisted of young people (mean age 22 years) and seniors (mean age 66 years) respectively. The third group included people who work with microscopes (mean age 44 years) . Forth group consisted of patients with diagnosed blepharitis (mean age 65 years). From every individual 3-4 lashes were epilated from the eyelids of both eyes and examined under the microscope for Demodex mites. The statistical analysis based on logistic regression was used to estimate the probability of infection. Age was independent variable significant for this model (p < 0.001). Significant relation between age and probability of Demodex infection was showed. The lowest number of infected individuals was observed in the group of young subjects (only 5%), the highest in the blepharitis patients (74% infected). Among microscope users 30% were infected, in the group of seniors 34% were infected.